Analisis Hukum Islam Terhadap Sistem Sewa Menyewa Di Rental Mobil Tom s Garage Kecamatan Kadipiro Surakarta - Nisaullatifah, Malia, Dr. Imron Rosyadi.,M.Ag (2016)
The objectives of the research are: 1) to know rental practice in Tom's Garage Car Rental and 2) to know rental practice in Tom's Garage viewed from Islam law. The type of this research is field reasearch with qualitative approach. The subjects of this research are the owner and finance staff in Tom's Garage. The data in this research are collected through observation, interview, and documentation. The process of analysis includes data collection, data reduction, data display, and conclusion / verification. The result of the research shows that the contract of car renting process is conducted by two sides, the owner as a person whose car being rented and the costumer as a person who rents a car. The implementation of down-payment is not on contrary with Islam syaria' as long there is an agreement between both sides. When there is a case of late or damage, the problem is solved through discussion and agreement. Both sides have their own responsibilities that have to be conducted. Keywords: Islam law, rental practice .